Takagi-Sugeno Fuzzy Approach in Rock Armored Slopes for 2% Wave Runup Estimation - Erdik, Tarkan; Savci, Mehmet Emin (Informa UK Limited, 2008)
Runup level exceeded by 2% of the incident waves is a key parameter in rough rock armored slopes design. From the literature survey, it is seen that the two most important factors influencing runup phenomena on rock armored slopes are structure permeability (SP) and surf similarity parameter (SSP). Since the relationships between wave runup and these parameters are complex, vague and uncertain in nature, it is quite difficult to adequately examine wave runup by conventional regressional approaches. Here, an attempt is made to construct various Takagi-Sugeno [TS, 1985] fuzzy models for predicting the 2% wave runup on rock armored slopes. The developed TS fuzzy model with two inputs namely SP and SSP yielded the best result out of all constructed models and is proposed in this study. The presented model is validated by comparison with widely used empirical model of Meer and Stam [MS, 1992], recommended by the U.S. Army Corps of Engineers [2002], using the experimental data-sets of MS. The verification process is obtained through scatter diagrams and two numerical error criterias. It was found that the TS model produce better accuracy in performance than the MS's empirical model.